2022
DOI: 10.1186/s13068-022-02150-w
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic screening and genomic mutation identification for enhancing cellulase production in Pichia pastoris

Abstract: Background Pichia pastoris is a widely used host organism for heterologous production of industrial proteins, such as cellulases. Although great progress has been achieved in improving protein expression in P. pastoris, the potential of the P. pastoris expression system has not been fully explored due to unknown genomic impact factors. Recently, whole-cell directed evolution, employing iterative rounds of genome-wide diversity generation and high-throughput screening (HTS), has been considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…To improve heterologous cellulase production in P. pastoris, a novel approach was developed based on the use of atmospheric and room-temperature plasma (ARTP) mutagenesis and a droplet-based microfluidic HTS system in whole-cell directed evolution. 82 The results indicated the best mutant strain R5-2 with a twofold increase in cellulase activity compared to the wild strain. Whole genome sequence analysis showed that a point mutation (Rsc1 V22G) was found in all topperforming variants.…”
Section: Directed Evolutionmentioning
confidence: 94%
See 1 more Smart Citation
“…To improve heterologous cellulase production in P. pastoris, a novel approach was developed based on the use of atmospheric and room-temperature plasma (ARTP) mutagenesis and a droplet-based microfluidic HTS system in whole-cell directed evolution. 82 The results indicated the best mutant strain R5-2 with a twofold increase in cellulase activity compared to the wild strain. Whole genome sequence analysis showed that a point mutation (Rsc1 V22G) was found in all topperforming variants.…”
Section: Directed Evolutionmentioning
confidence: 94%
“…Whole genome sequence analysis showed that a point mutation (Rsc1 V22G) was found in all topperforming variants. 82 From Chaetomella raphigera, the D2-BGL (⊎-glucosidase) gene was isolated via directed evolution and expressed in P. pastoris. Modified D2-BGL carried three novel mutations provided to have greater tolerance to substrate inhibition, higher V max value, enhanced specific activity, and higher protein titer as compared to wild-type enzyme.…”
Section: Directed Evolutionmentioning
confidence: 99%
“…[29] The agarose digital PCR original images in Figure 6c were provided by collaborators Dr. Xuefei Leng and Prof. Chaoyong Yang (College of Chemistry and Chemical Engineering, Xiamen University). [30] The original images in Figure 6d,e were captured from previously reported journal articles [31,32] respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with traditional microplate screening, the reagent cost was reduced by millions of times ( Lu et al, 2019 ). With atmospheric and room temperature plasma (ARTP) mutagenesis and droplet-based microfluidic high-throughput screening, it is possible to explore the potential of protein production by employing iterative rounds of genome-wide diversity generation ( Kenzom et al, 2015 ; Ma et al, 2019 ; Yuan et al, 2022 ). For example, compared to the beginning strain, the best mutant strain showed a twofold increase in cellulase activity in one research ( Yuan et al, 2022 ).…”
Section: High Throughput Screeningmentioning
confidence: 99%